Hubungan Persepsi Ibu, Dukungan Suami, Peran Petugas Kesehatan Dengan Anemia Di BPM Hj. Yetti Ruspiani, S.ST Kabupaten Lahat Tahun 2022: Relationship between Mother's Perception, Husband's Support, Role of Health Workers and Anemia in BPM Hj. Yetti Ruspiani, S.ST Lahat Regency in 2022 - Fransiska, Winda (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: The health of pregnant women as the 5th indicator in the Millennium Development Goals (MDG) launched by WHO has not been achieved because there are still 37.1% of pregnant women who experience anemia in Indonesia. The purpose of this study is to determine the relationship between maternal perception, husband support, and the role of health workers with anemia at BPM Hj. Yetti Ruspiani, S.ST lahat regency in 2022. Methods: This research is a quantitative type that is analytical in nature with a cross-sectional approach. This research was conducted at BPM Hj. Yetti Ruspiani, S.ST, Lahat Regency. The research time is June-August 2022. In this study, the population was pregnant women in BPM Hj. Yetti Ruspiani, S.ST of Lahat Regency as many as 80 people and samples using Accidental Sampling. Researchers used the Chi-Square test. Results: Based on the results of the study Frequency distribution, it is known that the majority of the incidence of anemia in pregnant women in BPM Hj. Yetti Ruspiani, S.ST Lahat Regency was 29 people (65,44%) and the number of non-anemic events in pregnant women was 16 people (35,6%). The results of the statistical test were 39 people (48,75%) and the number of non-anemic events in pregnant women was 41 people (51,25%). These results show that the number of pregnant women with a history of anemic events is greater than the number of pregnant women with a history of no incidence of anemia Based on the results of the study Frequency distribution, it is known that the majority of the incidence of anemia in pregnant women in BPM Hj. Yetti Ruspiani, S.ST Lahat Regency was 29 people (65,44%) and the number of non-anemic events in pregnant women was 16 people (35,6%). Discussion: The results of the statistical test were 39 people (48,75%) and the number of non-anemic events in pregnant women was 41 people (51,25%). These results show that the number of pregnant women with a history of anemic events is greater than the number of pregnant women with a history of no incidence of anemia.